Sociocultural Factors That Potentially Affect the Institution of Prevention and Treatment Strategies for Hepatitis B in Chinese Canadians - Harry Wu; Colina Yim; Alex Chan; Michael Ho; Jenny Heathcote (Canadian Journal of Gastroenterology)
BACKGROUND: Despite the availability of screening for chronic hepatitis B (CHB) infection and effective treatments now available, many at-risk individuals fail to seek appropriate medical attention.